Watching the watchdogs: Tracking SEC inquiries using geolocation data - William Gerken; Steven Irlbeck; Marcus Painter; Guangli Zhang (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2024)
The Securities and Exchange Commission's investigative process remains opaque and challenging to study due to limited observability. Leveraging de-identified smartphone geolocation data, we provide new insights into the SEC's monitoring practices by tracking SEC-associated devices that visit firm headquarters. Our findings reveal that the majority of SEC visits occur outside of formal investigations, with larger firms and those with a history of SEC enforcement actions being more frequently visited. These visits often cluster within industries. Notably, the SECassociated devices venture to firms both within and outside their own regions. On average, these visits are material, evidenced by significant stock price reactions, even in the absence of subsequent formal investigations or enforcement actions. Last, we observe a chilling effect on insider behavior around these SEC interactions; insiders are less likely to sell around visits. However, when sales do occur, insiders avoid substantial losses.
Keywords: 330; Finanzmarktaufsicht; Wirkungsanalyse; Kartographie; Insiderhandel; USA